Світська інтелектуальна еліта Гетьманщини у десятиліття модернізаційних проектів - Кононенко, В. (Український історичний збірник, 2010)
У статті на основі історіографічних та історичних джерел досліджено суспільно- політичні уявлення та ідеї козацьких інтелектуалів Гетьманщини 1760-х рр. Проаналізовано, що це десятиліття було «критичним» у реалізації концепції Малоросії та проекту Російської імперії. На 1760-ті рр., яскраво спостерігалася подвійна лояльність, що стала наслідком нерозривного зв’язку уявлення «вольностей» з іншою політичною ідеєю – службою православному протектору, який їх має оберігати. На цей час козацькі інтелектуали створили «схему» історії своєї Батьківщини, в основі якої лежало обґрунтування витоків та розвитку «малоросійських вольностей» від Русі, Великого князівства Литовського та Речі Посполитої до їх часу. У проектах Глухівської ради, творах світських інтелектуалів, наказах депутатам до Законодавчої комісії та їхній роботі у ній присутнє уявлення про Гетьманщину як фактично окрему державу у межах Російської імперії. В статье на основании историографических и архивных источников исследовано общественно-политические представления и идеи светских интеллектуалов Гетманщины 1760-х годов. Проанализировано, что на это десятилетие в среде светской интеллектуальной элиты Гетманщины возникли модернизационные проекты реформирования общественно- политической жизни, которые украинские интеллектуалы пытались вписать в условия Российской империи. Доказано, что представители светской интеллектуальной элиты Гетманщины были уверены, что именно их проекты «поправления отчизны» должны быть реализованы в общественно-политических реформах. The paper is devoted to analyze social-political imaginations and ideas of Cossack intellectuals of Hetmanate of 60-th XVIII century. Intellectuals were social group which were consisted of welleducated representatives of Cossack officers, Znachne military society and military clerks. It is indicated that the main factor of evolution of social-political imaginations and ideas of Cossack intellectuals of Hetmanate became modernization of Central-European societies. It is stated that modernization consisted in transformation of traditional society into modern one that was based on ideas of the «common wealth», «well-ordered state», clear laws, and practices of their realization. It is stated that Cossack intellectuals were convinced that their «draft of fatherland» must be incarnate in reforms of 60-th XVIII century social and political life of Hetmanate. In the projects of Glukhiv counsel, historical-literature texts of Cossack intellectuals, works of Legislative commission in 1767−1768 years Hetmanate presented as actually the separate state within the limits of the Russian empire. It is confirmed that social-political imagination and ideas of Cossack intellectuals were receipted other groups of Hetmanate society. It is emphasized that the basis of Little Russian identity base on loyalty to Orthodox monarchy and Motherland-Hetmanate.